GAMBARAN PENGELOLAAN LIMBAH B3 DI RSUD HAJI KOTA MAKASSAR - Sriyani Windarti (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2022)
Based on the results of the initial survey conducted in March 2021 at the Regional General Hospital (RSUD) Haji Makassar City produces B3 waste as much as ± 2 tons / month. At the Haji Makassar Regional General Hospital, the collection of B3 waste is still not carried out optimally, which is constrained in terms of separating the types of containers based on the type of waste. namely medical waste and nonmedical waste based on the provisions of the Minister of Health 1204/Menkes/SK/x/2004 concerning hospital environmental health requirements. The type of research used inThis research is a qualitative descriptive with an observational approach using secondary data collection methods from the environmental sanitation installation of IPSRS RSUD Haji Makassar. Collecting data from informants, informants in this study amounted to 5 informants. Researchers want to describe how the study of hazardous and toxic (B3) waste management at the Haji Hospital Makassar City in 2021. The results showed that the management of hospital B3 waste at the Haji Hospital of Makassar City was in accordance with Permenkes No. 101 of 2014 which regulates the management of B3 waste starting from the sorting and storage of B3 waste, B3 waste storage, B3 waste collection, B3 waste treatment, and transportation of B3 waste. The suggestion from the researcher is that in managing Hazardous and Toxic (B3) waste, it is better to carry out the packaging process until the transportation of B3 waste is carried out as well as possible to reduce the accumulation of B3 waste that can harm the surrounding environment.